2021
DOI: 10.1016/j.wroa.2021.100091
|View full text |Cite
|
Sign up to set email alerts
|

Demonstrating the reduction of enteric viruses by drinking water treatment during snowmelt episodes in urban areas

Abstract: This study investigates short-term fluctuations in virus concentrations in source water and their removal by full-scale drinking water treatment processes under different source water conditions. Transient peaks in raw water faecal contamination were identified using in situ online β- d -glucuronidase activity monitoring at two urban drinking water treatment plants. During these peaks, sequential grab samples were collected at the source and throughout the treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…We believe that this should not be taken into account, as we used extremely contaminated water. Cytopathic effect can be caused by a variety of enteric viruses ( Sylvestre et al, 2021 ) and is not necessarily evidence of viable SARS-CoV-2.…”
Section: Discussionmentioning
confidence: 99%
“…We believe that this should not be taken into account, as we used extremely contaminated water. Cytopathic effect can be caused by a variety of enteric viruses ( Sylvestre et al, 2021 ) and is not necessarily evidence of viable SARS-CoV-2.…”
Section: Discussionmentioning
confidence: 99%
“…There are other online monitors such as turbidity and particle-size distribution which are being used in a diagnostic capacity by drinking water treatment plants (DWTPs) operators for monitoring raw and treated water quality. Interesting applications showed that elevated water flow levels linked to rainfall or snowmelt events increased the viral and phage concentrations in a catchment (Fauvel et al, 2016 ; Sylvestre et al, 2021 ). Infectious F-specific RNA bacteriophage concentrations increased during rainfall events (Fauvel et al, 2016 ), whereas viral concentrations increased by ~0.5-log during two snowmelt/rainfall episodes and ~1.0-log following a planned wastewater discharge upstream of the drinking water intake (Sylvestre et al, 2021 ).…”
Section: Online Monitoring Tools: Limitations Future Outlook and Reco...mentioning
confidence: 99%
“…Interesting applications showed that elevated water flow levels linked to rainfall or snowmelt events increased the viral and phage concentrations in a catchment (Fauvel et al, 2016 ; Sylvestre et al, 2021 ). Infectious F-specific RNA bacteriophage concentrations increased during rainfall events (Fauvel et al, 2016 ), whereas viral concentrations increased by ~0.5-log during two snowmelt/rainfall episodes and ~1.0-log following a planned wastewater discharge upstream of the drinking water intake (Sylvestre et al, 2021 ). Another approach is to utilize enzyme-based sensors specific to coliforms.…”
Section: Online Monitoring Tools: Limitations Future Outlook and Reco...mentioning
confidence: 99%
See 1 more Smart Citation
“…Environmental water is often contaminated with wastewater from cities or farms and may contain both human and animal pathogens. Rotaviruses are viral agents that cause severe diarrheal disease and death in infants, children, and young animals ( Dhama et al, 2009 ) and have been detected in both surface and groundwater sources ( Miura et al, 2019 , 2021 ; Sylvestre et al, 2021 ). Rotaviruses have been identified as potential reference pathogens in the WHO Guidelines for Drinking-Water Quality ( WHO, 2017 ).…”
Section: Introductionmentioning
confidence: 99%